Rozwój kreatywności wyzwaniem XXI wieku a rzeczywistość szkoły = Development of creativity as a challenge for the 21st century and school reality - Olczak, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the era of technological development and increasing demand for creativity and innovation, expectations placed on education in this respect are growing (or should grow). In addition to numerous competencies, including intellectual or social ones, one should expect that school will develop students` abilities to think independently, criticise, conclude, design, or programme, i.e. skills connected with and contributing to human creativity. The article analyses how school deals with this challenge. It attempts to establish whether and how school develops students? potential in this area. The article shows how important it is to care for the development of the attitude of openness and creativity in contemporary people. It also attempts to formulate expectations for education and simultaneously contrasts them with the current reality of schools. The author aims to show what possibilities school has in this respect, how they are used, and in what areas time is wasted in children?s and adolescents? development.
Keywords: kreatywność; rozwój; potencjał ucznia; wyzwania edukacyjne; creativity; development; student`s potential; educational challenges